Case Report of a de Novo Mutation of PCDH19 in Saudi Family Limited to Females - Alsheikh, MD, Rawan; Al-Qassmi, MD, Amal (International Journal of Innovative Research in Medical Science, 2021)
Up to date more than 60 different mutations in PCDH19 have been identified. Most of PCDH19 gene is located in Xq22 and produces nonclustered delta protocadherin. This disorder primarily manifests in heterozygote females due to random X chromosome inactivation leading to somatic mosaicism and abnormal cellular interference between cells with and without delta-protocadherin., but we a heterozygous nucleotide mutation causing amino acid 561 to change from Pro to Ser (p.Pro561Ser). This mutation was de novo, and this alteration was not found in her parents. PCDH19-related epilepsy is a distinct childhood-onset epilepsy syndrome characterized by brief clusters of febrile and afebrile seizures with onset primarily before the age of three years, cognitive impairment, autistic traits, and behavioral abnormalities. We describe the features of a de novo mutation in 3 sibling, presented with early onset of seizure, two of them were controlled and wean off medication was at age of six year and her sister at age of 10 year .The youngest sister still partially controlled on medication, she had seizure only during febrile illness.